Suitability of pollen sources for the development and reproduction of Coleomegilla maculata (Coleoptera: Coccinellidae) under simulated drought conditions - Michaud, J. P.; Grant, Angela K. (My University, 2012)
Laboratory experiments compared the nutritive value of various pollen sources for the development of Coleomegilla maculata DeGeer under conditions of continuous water availability and simulated drought. When water was continuously available, larval survival was not diVerent from 100% on diets of frozen eggs of Ephestia kuehniella Zeller, corn pollen, sorghum pollen, or pulverized bee pollen, whereas survival of larvae was signiWcantly reduced on the latter three diets in the simulated drought treatment. Pollen of cultivated sunXower, Helianthus annus L., proved fatal to both larvae and adults; its surface structure caused clumping and accumulation on the insect cuticle that led to death from exhaustion/desiccation in petri dishes. The Ephestia egg diet yielded shorter developmental times and heavier adult weights than any pollen diet in both treatments. The drought treatment increased developmental time on all diets with a signiWcant treatment–diet interaction. Drought reduced the adult weight of females on the sorghum pollen diet, and that of both sexes on the bee pollen diet, again with a signiWcant treatment–diet interaction. Initial water content was highest in corn pollen (36.8%), followed by Ephestia eggs (29.2%), sorghum pollen (25.3%), sunXower pollen (8.7%), and bee pollen (4.6%), but did not appear correlated with C. maculata larval survival on pollen sources under drought conditions. Reproductive adult females that received corn or sorghum pollen as a supplement to Ephestia eggs did not diVer in fecundity or fertility from those fed only Ephestia eggs.
Citation: Michaud, J.P., & Grant, A.K. (2005). Suitability of pollen sources for the development and reproduction of Coleomegilla maculata (Coleoptera: Coccinellidae) under simulated drought conditions. Biological Control, 32(3), 363-370.
Keywords: Coleomegilla maculata; Development; Drought; Helianthus annus; Pollen; Reproduction; Sorghum bicolor; Zea mays